2009
DOI: 10.1002/marc.200900494
|View full text |Cite
|
Sign up to set email alerts
|

Star‐Shaped Polyacrylates: Highly Functionalized Architectures via CuAAC Click Conjugation

Abstract: Well-defined functional star-shaped polymer structures with up to 29 arms have been successfully synthesized by the combination of atom transfer radical polymerization (ATRP) and click chemistry. First, azide end-functionalized poly(isobornyl acrylate) (PiBA) star-shaped polymers were prepared by successive ATRP and bromine substitution. Subsequently, alkyne end-functionalized molecules and polymers were introduced onto the star-shaped PiBA bearing pendant azide moieties by copper-catalyzed azide-alkyne cycloa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 50 publications
0
29
0
Order By: Relevance
“…Well‐defined three‐arm star block copolymers could be synthesized in at least three different ways: diblock arms could be grown divergently from a core molecule, preformed linear diblocks could be coupled to a functionalized core, or homopolymer arms could be coupled to the ends of a functionalized three‐arm star homopolymer 54. The last of these three approaches was tested by coupling linear PEG to a PCL three‐arm star core (Scheme )…”
Section: Resultsmentioning
confidence: 99%
“…Well‐defined three‐arm star block copolymers could be synthesized in at least three different ways: diblock arms could be grown divergently from a core molecule, preformed linear diblocks could be coupled to a functionalized core, or homopolymer arms could be coupled to the ends of a functionalized three‐arm star homopolymer 54. The last of these three approaches was tested by coupling linear PEG to a PCL three‐arm star core (Scheme )…”
Section: Resultsmentioning
confidence: 99%
“…Besides, click chemistry reactions can link particular groups or compounds together through triazole ring and fabricate functional materials. Recently it becomes a very powerful tool in the modification of nano-materials and carbohydrate compounds [8][9][10][11], also in the construction of star polymers [12][13][14][15][16][17][18][19] and polyurethane [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The reactivity and the grafting rate are moderate. Compared with above methods, click reaction, defined by Sharpless and coworkers,26 offers a powerful method for the controlled manipulation of macromolecular architecture and polymer synthesis because of its quantitative yields, mild reaction condition, and tolerance of a wide range of functional groups 27–36. Recent works by Du Prez have shown that “click” chemistry is a promising tool for side‐chain functionalization of polyurethanes 37, 38…”
Section: Introductionmentioning
confidence: 99%
“…Compared with above methods, click reaction, defined by Sharpless and coworkers, 26 offers a powerful method for the controlled manipulation of macromolecular architecture and polymer synthesis because of its quantitative yields, mild reaction condition, and tolerance of a wide range of functional groups. [27][28][29][30][31][32][33][34][35][36] Recent works by Du Prez have shown that ''click'' chemistry is a promising tool for sidechain functionalization of polyurethanes. 37,38 We are interested in synthesizing blood compatible polyurethane containing zwitterionic sulfobetaine groups as potential candidate for short-term bloodcontacting applications.…”
Section: Introductionmentioning
confidence: 99%